Familial dysalbuminemic hyperthyroxinemia confounding management of coexistent autoimmune thyroid disease. (26th February 2020) - Khoo, Serena; Lyons, Greta; Solomon, Andrew; Oddy, Susan; Halsall, David; Chatterjee, Krishna; Moran, Carla
Abstract : Summary: Familial dysalbuminemic hyperthyroxinemia (FDH) is a cause of discordant thyroid function tests (TFTs), due to interference in free T4 assays, caused by the mutant albumin. The coexistence of thyroid disease and FDH can further complicate diagnosis and potentially result in inappropriate management. We describe a case of both Hashimoto's thyroiditis and Graves' disease occurring on a background of FDH. A 42-year-old lady with longstanding autoimmune hypothyroidism was treated with thyroxine but in varying dosage, because TFTs, showing high Free T4 (FT4) and normal TSH levels, were discordant. Discontinuation of thyroxine led to marked TSH rise but with normal FT4 levels. She then developed Graves' disease and thyroid ophthalmopathy, with markedly elevated FT4 (62.7 pmol/L), suppressed TSH (<0.03 mU/L) and positive anti-TSH receptor antibody levels. However, propylthiouracil treatment even in low dosage (100 mg daily) resulted in profound hypothyroidism (TSH: 138 mU/L; FT4: 4.8 pmol/L), prompting its discontinuation and recommencement of thyroxine. The presence of discordant thyroid hormone measurements from two different methods suggested analytical interference. Elevated circulating total T4 (TT4), (227 nmol/L; NR: 69–141) but normal thyroxine binding globulin (TBG) (19.2 µg/mL; NR: 14.0–31.0) levels, together with increased binding of patient's serum to radiolabelled T4, suggested FDH, and ALB sequencing confirmed a causal albumin variant (R218H). This case highlights difficulty ascertaining true thyroid status in patients with autoimmune thyroid disease and coexisting FDH. Early recognition of FDH as a cause for discordant TFTs may improve patient management. Learning points: The typical biochemical features of familial dysalbuminemic hyperthyroxinemia (FDH) are (genuinely) raised total and (spuriously) raised free T4 concentrations due to enhanced binding of the mutant albumin to thyroid hormones, with normal TBG and TSH concentrations. Given the high prevalence of autoimmune thyroid disease, it is not surprising that assay interference from coexisting FDH may lead to discordant thyroid function tests confounding diagnosis and resulting in inappropriate therapy. Discrepant thyroid hormone measurements using two different immunoassay methods should alert to the possibility of laboratory analytical interference. The diagnosis of FDH is suspected if there is a similar abnormal familial pattern of TFTs and increased binding of radiolabelled 125I-T4 to the patient's serum, and can be confirmed by ALB gene sequencing. When autoimmune thyroid disease coexists with FDH, TSH levels are the most reliable biochemical marker of thyroid status. Measurement of FT4 using equilibrium dialysis or ultrafiltration are more reliable but less readily available.